1996
DOI: 10.1099/00221287-142-4-741
|View full text |Cite
|
Sign up to set email alerts
|

Two multifunctional peptide synthetases and an O-methyltransferase are involved in the biosynthesis of the DNA-binding antibiotic and antitumour agent saframycin Mx1 from Myxococcus xanthus

Abstract: Saframycin M x l is a DNA-binding antibiotic and antitumour agent produced by Myxococcus xanthus. It is a heterocyclic quinone, thought to be synthesized via the linear pepide intermediate AlaGlyTyrTyr. Analysis of 14-1 kb DNA sequence involved in saframycin production revealed genes for two large multifunctional peptide synthetases of 1770 and 2605 amino acids, respectively, and a putative 0-methyltransferase of 220 amino acids. The three ORFs read in the same direction and are separated by short non-translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 36 publications
1
61
0
3
Order By: Relevance
“…Previous studies on SFM-Mx1 and SAC-B biosynthesis revealed a relatively rare reductase (RE) domain that contains a NAD(P)H binding site at the C-terminal ends of SafA and SacC (33,46), both of which are NRPSs involved in the tetrapeptidyl backbone formation. These RE domains may act on the PCP-tethered polypeptidyl intermediate and reductively release it from the PCP as a linear aldehyde (21), instead of the thioesterase (TE) functionality at the C-terminal ends of typical NRPSs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on SFM-Mx1 and SAC-B biosynthesis revealed a relatively rare reductase (RE) domain that contains a NAD(P)H binding site at the C-terminal ends of SafA and SacC (33,46), both of which are NRPSs involved in the tetrapeptidyl backbone formation. These RE domains may act on the PCP-tethered polypeptidyl intermediate and reductively release it from the PCP as a linear aldehyde (21), instead of the thioesterase (TE) functionality at the C-terminal ends of typical NRPSs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the colinearity rule (25), wherein the NRPS module organization parallels the order of the amino acid residues in the resultant polypeptide, sequential incorporation of Ala, Gly, and two Tyr derivatives into the tetrapeptide in SAM-Mx1 biosynthesis was previously speculated to be directed by four successive modules (i.e., SafB-AL-PCP0, SafB-C1-A1-PCP1, SafA-C2-A2-PCP2, and SafA-C3-A3-PCP3-RE) (Fig. 6B) (33). Since SacA in SAC-B biosynthesis lacks the first module AL-PCP0, a bifunctional adenylation activation by SacA or direct incorporation of an Ala-Gly dipeptide into the tetrapeptide by SacA was hypothesized ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reductive mechanism terminating nonribosomal peptide biosynthesis has been described for myxochelin in Stigmatella aurantiaca Sg a15 (Gaitatzis et al, 2001), and for saframycin Mx1 in Myxococcus xanthus (Pospiech et al, 1996).…”
Section: Formation Of the CM Hydroxymethyl Groupmentioning
confidence: 99%
“…29,30 To date, three biosynthetic gene clusters of tetrahydroisoquinoline antibiotics 14, safracin B ( Figure 5, 16) and saframycin Mx1 (17) have been identified and their bioinfomatic analysis indicated that a saframycin backbone is constructed by NRPS. 30,31,32 Recently, Wen and coworkers proposed that the saframycin NRPS (SfmA, SfmB, SfmC) unusually assembles the core skeleton via a putative tetrapeptidyl intermediate using SfmC in an iterative manner. 32 However, detailed biosynthetic mechanism of this unusual transformation has not been uncovered.…”
Section: Enzymatic Synthesis Of Core Skeleton Of Antitumor Antibioticmentioning
confidence: 99%